No longer at ease - Achebe, Chinua, 1930-; Penguin Books (London : Penguin Books, 2010)
Obi Okonkwo feels separated from his African roots because of his education, and he is forced to choose between his culture's traditional values and the demands of his social class.
English.
Keywords: City and town life -- Fiction